New energy vehicle high-temperature heat stable cable and high-temperature heat stabilization method

CN123017627APending Publication Date: 2026-10-30TRI WIRE SCI CO LTD DONGGUAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611482222.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

电缆在频繁启停和冷热循环过程中,导体、绝缘层、屏蔽层和护套层之间因热膨胀系数不同而产生界面应力,容易导致绝缘层剥离、微裂纹和界面空隙,进一步恶化导热和绝缘性能

Benefits of technology

与现有技术相比,本发明不是单纯依赖提高绝缘材料本身耐温等级,而是通过复合耐热绝缘层、导热过渡层和屏蔽/散热复合层形成由内向外的梯级导热散热路径。复合耐热绝缘层中的纳米氮化硼能够提高绝缘层内部导热能力,导热过渡层降低绝缘层与屏蔽层之间的界面热阻,屏蔽/散热复合层中的镀镍铜丝编织层和导热石墨带层能够将热量向电缆外表面快速扩散,由此显著降低导体附近局部过热风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017627A_ABST
    Figure CN123017627A_ABST
Patent Text Reader

Abstract

The application discloses a new energy automobile high-temperature heat-stable cable and a preparation method thereof, and belongs to the technical field of new energy automobile high-voltage cables. The cable comprises, from inside to outside, a conductor, a composite heat-resistant insulation layer, a heat-conducting transition layer, a shielding / heat-dissipating composite layer and an outer sheath layer. The composite heat-resistant insulation layer adopts a methyl vinyl silicone rubber / fluoroelastomer blending system, and gas-phase white carbon black, nano boron nitride, nano cerium oxide, a silane coupling agent and a crosslinking agent are added; the heat-conducting transition layer is arranged between the composite heat-resistant insulation layer and the shielding / heat-dissipating composite layer, and is used for reducing interface thermal resistance; and the shielding / heat-dissipating composite layer comprises a nickel-plated copper wire braiding layer and a heat-conducting graphite tape layer. The preparation method comprises insulating material mixing, insulating layer extrusion, irradiation crosslinking, heat-conducting transition layer coating or co-extrusion, shielding / heat-dissipating composite layer preparation and outer sheath extrusion. The application forms a step-by-step heat-conducting and heat-dissipating path from inside to outside, and improves the high-temperature resistance, heat-aging resistance and operation safety of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable manufacturing technology, and in particular to a high-temperature thermally stable cable for new energy vehicles and a high-temperature thermal stabilization method. Background Technology

[0002] High-voltage cables for new energy vehicles are mainly used to connect key components such as power battery packs, motor controllers, drive motors, on-board chargers, high-voltage distribution boxes, and air conditioning compressors. Compared with traditional low-voltage automotive cables, high-voltage cables for new energy vehicles typically carry higher voltages and larger currents, and operate for extended periods in engine compartments, near battery packs, chassis tunnels, or other high-temperature, enclosed spaces. Therefore, these cables not only need to possess excellent electrical insulation properties, but also superior resistance to high temperatures, oil, aging, bending, and safety.

[0003] The insulation materials used in existing new energy vehicle cables are mostly cross-linked polyolefins, silicone rubber, or other elastomers. While these materials can meet certain temperature resistance requirements under normal operating conditions, in environments with sustained high temperatures, high currents, and limited heat dissipation, the combined effect of conductor resistive heat and ambient heat can easily keep the insulation layer at a high temperature for extended periods. Sustained high temperatures accelerate the thermo-oxidative degradation of polymer molecular chains, leading to hardening, cracking, decreased elongation, and reduced insulation resistance in the insulation layer. In severe cases, this can cause localized breakdown or safety accidents.

[0004] Furthermore, the compact interior space of new energy vehicles often results in cables being bundled together, making it difficult to dissipate heat effectively. While the metal braided shielding layer in existing cables possesses some thermal conductivity, its primary function remains electromagnetic shielding, failing to form a systematic heat dissipation structure with the insulation layer and outer sheath. During frequent start-stop cycles and thermal cycling, the different coefficients of thermal expansion between the conductor, insulation layer, shielding layer, and sheath layer generate interfacial stresses, easily leading to insulation peeling, microcracks, and interfacial voids, further deteriorating thermal conductivity and insulation performance. Summary of the Invention

[0005] To address the aforementioned issues, this invention provides a high-temperature thermally stable cable for new energy vehicles, which forms a stepped heat conduction and dissipation path from the inside out, thereby improving the cable's resistance to high temperatures, heat aging, and operational safety, as well as a high-temperature thermal stabilization method.

[0006] The technical solution adopted in this invention is: a high-temperature thermally stable cable for new energy vehicles, comprising, from the inside out, a conductor, a composite heat-resistant insulation layer, a thermally conductive transition layer, a shielding / heat dissipation composite layer, and an outer sheath layer; the composite heat-resistant insulation layer comprises a silicone rubber / fluoroelastomer blend matrix, fumed silica, nano-boron nitride, nano-cerium oxide, a silane coupling agent, and a crosslinking agent; the thermally conductive transition layer is disposed between the composite heat-resistant insulation layer and the shielding / heat dissipation composite layer to reduce the interfacial thermal resistance between the composite heat-resistant insulation layer and the shielding / heat dissipation composite layer; the shielding / heat dissipation composite layer comprises a nickel-plated copper wire braided layer and a thermally conductive graphite tape layer; The composite heat-resistant insulation layer, the thermally conductive transition layer, and the shielding / heat dissipation composite layer together form a stepped heat conduction and heat dissipation path that conducts heat from the conductor to the outer sheath layer.

[0007] A further improvement to the above scheme is that the conductor is bare copper stranded wire, nickel-plated copper stranded wire, or silver-plated copper stranded wire, and the conductor cross-sectional area is 16-120 mm²; preferably, the conductor is nickel-plated copper stranded wire.

[0008] A further improvement to the above scheme is that it also includes an inner semiconductive shielding layer, which is disposed between the conductor and the composite heat-resistant insulation layer to homogenize the electric field on the conductor surface and reduce the local electric field concentration caused by the conductor stranding gap.

[0009] A further improvement to the above scheme is that the silicone rubber / fluoroelastomer blend matrix includes methyl vinyl silicone rubber and fluoroelastomer, wherein, based on a total weight of 100 parts of methyl vinyl silicone rubber and fluoroelastomer, the methyl vinyl silicone rubber comprises 60 to 80 parts and the fluoroelastomer comprises 20 to 40 parts.

[0010] A further improvement to the above scheme is that, based on 100 parts of the total weight of the methyl vinyl silicone rubber and fluoroelastomer, the composite heat-resistant insulating layer further includes: 20-40 parts of fumed silica; 5-20 parts of nano boron nitride; 1-5 parts of nano-cerium oxide; 1-3 parts of silane coupling agent; Crosslinking agent 0.5 to 2 parts.

[0011] A further improvement to the above scheme is that the nano boron nitride is hexagonal boron nitride with a particle size of 100-300 nm; The particle size of the nano-cerium oxide is 20–80 nm; The silane coupling agent is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, aminosilane, and epoxysilane; The crosslinking agent is 2,5-dimethyl-2,5-di-tert-butylperoxide.

[0012] A further improvement to the above scheme is that the thickness of the thermally conductive transition layer is 0.1–0.5 mm; The thermally conductive transition layer is a thermally conductive silicone grease layer or a thermally conductive elastomer layer. The thermally conductive transition layer includes a silicone rubber matrix, spherical alumina filler, and nano boron nitride. The particle size of the spherical alumina filler is 1 to 10 μm. The thermal conductivity of the thermally conductive transition layer is not less than 1.5 W / m·K.

[0013] A further improvement to the above scheme is that the braiding density of the nickel-plated copper wire braid layer is not less than 85%; The thermally conductive graphite tape layer is wrapped around or longitudinally wrapped around the outside of the nickel-plated copper wire braided layer. The thickness of the thermally conductive graphite tape layer is 0.1 to 0.3 mm, and the in-plane thermal conductivity is not less than 300 W / m·K.

[0014] A further improvement to the above scheme is that the thermally conductive graphite tape layer is spirally wrapped along the cable axis, and the adjacent wrapping edges have an overlapping area; or, the thermally conductive graphite tape layer is longitudinally wrapped along the cable axis, and the outer side of the longitudinal wrapping overlapping edge is pressed and fixed by the outer sheath layer.

[0015] A further improvement to the above scheme is that the outer sheath layer is an irradiated cross-linked polyolefin sheath layer or a silicone rubber sheath layer, and the outer sheath layer also includes one or more of nano boron nitride, flame retardant, antioxidant and wear-resistant additive.

[0016] A further improvement to the above scheme is that the composite heat-resistant insulation layer is cross-linked by electron beam irradiation to form a cross-linked network structure, and the long-term temperature resistance of the cable is not lower than 150℃.

[0017] A method for high-temperature thermal stabilization of cables for new energy vehicles, used to prepare high-temperature thermally stable cables for new energy vehicles, includes the following steps: S1. Preparation of composite heat-resistant insulation material: Methyl vinyl silicone rubber and fluoroelastomer are put into a mixing equipment and mixed at 120-150℃ for 5-10 minutes. Then, fumed silica, nano boron nitride, nano cerium oxide and silane coupling agent are added in sequence and mixed for another 15-20 minutes. After cooling, a crosslinking agent is added. After thinning, cooling and pelletizing, the composite heat-resistant insulation material is obtained. S2. Extrusion of composite heat-resistant insulation layer: The composite heat-resistant insulation material is coated onto the outer periphery of the conductor through an extrusion device to form a composite heat-resistant insulation layer; S3, Crosslinking treatment: Electron beam irradiation is performed on the insulated wire core that forms the composite heat-resistant insulation layer for crosslinking. S4. Forming a thermally conductive transition layer: Coating or co-extruding a thermally conductive transition layer around the outer periphery of the composite heat-resistant insulation layer; S5. Forming a shielding / heat dissipation composite layer: First, nickel-plated copper wire is woven around the outer periphery of the thermally conductive transition layer to form a nickel-plated copper wire braided layer, and then thermally conductive graphite tape is wrapped around or longitudinally wrapped to form a thermally conductive graphite tape layer. S6. Extruded outer sheath layer: An outer sheath layer is extruded around the outer periphery of the shielding / heat dissipation composite layer.

[0018] A further improvement to the above scheme is that, in step S2, the extrusion temperature of the composite heat-resistant insulation layer is: 100-120℃ in the feeding section, 130-160℃ in the plasticizing section, 150-180℃ in the homogenizing section, and 160-180℃ in the die head.

[0019] A further improvement to the above scheme is that, in step S3, the irradiation dose for electron beam crosslinking is 80–200 kGy.

[0020] A further improvement to the above scheme is that, after step S6, the outer sheath layer is subjected to irradiation crosslinking treatment, and / or the resulting cable is subjected to high-temperature aging test, thermal cycling test, insulation resistance test, and conductor-to-outer surface temperature difference test.

[0021] The beneficial effects of this invention are: Compared to existing technologies, this invention does not simply rely on increasing the temperature resistance of the insulation material itself. Instead, it forms a stepped heat conduction and dissipation path from the inside out through a composite heat-resistant insulation layer, a thermally conductive transition layer, and a shielding / heat dissipation composite layer. The nano-boron nitride in the composite heat-resistant insulation layer enhances the internal thermal conductivity of the insulation layer; the thermally conductive transition layer reduces the interfacial thermal resistance between the insulation and shielding layers; and the nickel-plated copper wire braid and thermally conductive graphite tape layers in the shielding / heat dissipation composite layer rapidly diffuse heat to the outer surface of the cable, thereby significantly reducing the risk of localized overheating near the conductor.

[0022] The composite heat-resistant insulation layer uses a blend of methyl vinyl silicone rubber and fluoroelastomer. The silicone rubber provides a high-temperature elastic skeleton, while the fluoroelastomer improves high-temperature mechanical strength, oil resistance, and chemical resistance. After cross-linking by electron beam irradiation, the two form a cross-linked network structure, which enables the insulation layer to maintain good dimensional stability and mechanical integrity under high-temperature environments, thus helping to improve the long-term temperature resistance of the cable to 150℃ or above.

[0023] This invention simultaneously introduces nano-boron nitride and nano-cerium oxide into a composite heat-resistant insulating layer. Nano-boron nitride possesses high thermal conductivity and electrical insulation properties, enabling it to form microscopic thermal conductive pathways within the insulating material, reducing the accumulation of heat within the insulating layer; nano-cerium oxide contains Ce³⁺. + / Ce 4+ Variable valence states can capture and quench free radicals generated during high-temperature thermal oxidation, thus delaying polymer chain degradation. These two factors work synergistically to form a thermal stabilization mechanism of "active heat conduction and cooling + inhibition of thermo-oxidative degradation."

[0024] A thermally conductive transition layer is positioned between the composite heat-resistant insulation layer and the shielding / heat dissipation composite layer. It fills the microscopic gaps between the insulation layer and the metal braided layer or graphite tape, reducing interfacial thermal resistance and allowing heat from the insulation layer to be transferred more smoothly to the external heat dissipation layer. Simultaneously, the thermally conductive transition layer possesses a certain degree of elasticity, which can buffer the thermomechanical stress generated between the silicone rubber / fluoroelastomer insulation layer and the metal shielding layer due to the difference in their coefficients of thermal expansion, reducing interfacial peeling, cracking, and the formation of localized voids.

[0025] The shielding / heat dissipation composite layer combines a nickel-plated copper wire braid layer with a thermally conductive graphite tape layer. The nickel-plated copper wire braid layer not only provides electromagnetic shielding but also serves as a heat collection and conduction network; the thermally conductive graphite tape layer has high in-plane thermal conductivity, which can rapidly expand localized point heat into a surface heat flow, thereby improving the uniformity of temperature distribution on the outer sheath surface and reducing the risk of accelerated insulation aging caused by localized hot spots.

[0026] The composite heat-resistant insulation layer of this invention uses silicone rubber as a high-temperature elastic skeleton and introduces an appropriate amount of fluoroelastomer to enhance high-temperature mechanical properties and oil resistance. It does not use excessively high-filling rigid materials as the only heat-resistant means, thus it can maintain good flexibility while improving heat resistance and thermal conductivity. It is suitable for high-voltage cables of new energy vehicles to bend and be routed in confined spaces and in long-term vibration environments.

[0027] Electron beam irradiation crosslinking forms a stable crosslinked network between VMQ and FKM molecular chains. Simultaneously, the silane coupling agent enhances the interfacial bonding between the nanofiller and the matrix, making it less prone to migration and aggregation of nano-boron nitride and nano-cerium oxide under long-term high-temperature service conditions. This improves the cable insulation's resistance to heat deformation, heat aging retention, and electrical insulation stability.

[0028] Because cables are more prone to heat accumulation, insulation degradation, and local breakdown in high-temperature, high-current, enclosed, and vibrating environments, this invention reduces the risk of long-term overheating operation and improves the safety and reliability of high-voltage cable systems for new energy vehicles through a comprehensive design that integrates material thermal stability, internal heat conduction, interface heat conduction, and external diffusion heat dissipation. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the structure of the high-temperature thermally stable cable for new energy vehicles according to the present invention; Figure 2 This is a schematic diagram of another embodiment of the high-temperature thermally stable cable for new energy vehicles according to the present invention; Figure 3 This is a schematic flowchart of the high-temperature thermal stabilization method for new energy vehicle cables according to the present invention.

[0030] Explanation of reference numerals in the attached figures: Conductor 1; Composite heat-resistant insulation layer 2; Thermally conductive transition layer 3; Shielding / heat dissipation composite layer 4, nickel-plated copper wire braided layer 41, thermally conductive graphite tape layer 42; Outer sheath layer 5; 6. Inner semiconductive shielding layer. Detailed Implementation

[0031] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the invention.

[0032] It should be noted that when a component is said to be "fixed to" another component, it can be directly attached to the other component or there may be an intervening component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there may be an intervening component.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0034] like Figures 1-3 As shown, this invention provides a high-temperature thermally stable cable for new energy vehicles. This cable is mainly used for power transmission between high-voltage systems such as power batteries, motor controllers, drive motors, on-board chargers, and high-voltage distribution boxes in new energy vehicles. This cable is particularly suitable for use under conditions of long-term exposure to high temperatures, high currents, confined spaces, frequent thermal cycling, and vibration. The cable of this invention comprises, from the inside out, a conductor 1, a composite heat-resistant insulation layer 2, a thermally conductive transition layer 3, a shielding / heat dissipation composite layer 4, and an outer sheath layer 5. In some embodiments, an inner semi-conductive shielding layer 6 can be provided between the conductor 1 and the composite heat-resistant insulation layer 2 to homogenize the electric field on the conductor surface and reduce localized electric field concentration caused by unevenness on the stranded conductor surface.

[0035] The core concept of this invention is that the cable no longer relies solely on improving the temperature resistance of the insulation material itself to cope with high temperatures, but rather improves thermal stability from both the material and structural levels. On one hand, the composite heat-resistant insulation layer 2 adopts a VMQ / FKM blend system and introduces nano-boron nitride and nano-cerium oxide to achieve dual modification of thermal conductivity and heat resistance. On the other hand, a thermally conductive transition layer 3 is set outside the insulation layer, and a shielding / heat dissipation composite layer 4 composed of a nickel-plated copper wire braided layer 41 and a thermally conductive graphite tape layer 42 is further set, so that the heat generated by the conductor can be transferred to the external environment more efficiently in both the radial and axial directions.

[0036] This creates a stepped heat dissipation path inside the cable: conductor—composite heat-resistant insulation layer—thermally conductive transition layer—nickel-plated copper wire braided layer—thermally conductive graphite tape layer—outer sheath layer. This path reduces the temperature gradient between the conductor and the outer side of the insulation layer, minimizing the time the insulation layer is exposed to localized high temperatures, thus delaying thermal aging.

[0037] Conductor 1 can be bare copper stranded wire, nickel-plated copper stranded wire, or silver-plated copper stranded wire. The conductor cross-sectional area can be designed from 16 to 120 mm² according to the cable's current carrying capacity. For example, for lower power branches, 16 mm², 25 mm², or 35 mm² conductors can be used; for main power circuits, 50 mm², 70 mm², 95 mm², or 120 mm² conductors can be used.

[0038] Preferably, conductor 1 is made of nickel-plated copper stranded wire. The nickel plating layer can improve the oxidation resistance of the copper conductor in high temperature and humid environments, reduce the formation of oxide layer on the conductor surface, and maintain low contact resistance and stable conductivity. Conductor 1 adopts a multi-strand stranded structure to improve the cable's flexibility and bending resistance.

[0039] In embodiments where an inner semiconductive shielding layer 6 is provided, the inner semiconductive shielding layer 6 can be made of semiconductive silicone rubber or semiconductive cross-linked polyolefin material extruded onto the outer periphery of the conductor 1. This layer can fill the irregular gaps on the outer periphery of the stranded conductor, making the electric field distribution more uniform and improving the insulation reliability of the cable under high-voltage conditions.

[0040] The composite heat-resistant insulating layer 2 is the key functional layer of this invention. This layer includes a silicone rubber / fluoroelastomer blend matrix, fumed silica, nano boron nitride, nano cerium oxide, silane coupling agent, and crosslinking agent.

[0041] The silicone rubber / fluoroelastomer blend matrix includes methyl vinyl silicone rubber and fluoroelastomer. Based on a total weight of 100 parts, methyl vinyl silicone rubber comprises 60–80 parts, and fluoroelastomer comprises 20–40 parts.

[0042] Methyl vinyl silicone rubber possesses excellent high-temperature elasticity and low-temperature flexibility, making it suitable as the basic elastic skeleton for insulation layers. Fluoroelastics exhibit good oil resistance, chemical resistance, and high-temperature mechanical strength, compensating for the shortcomings of single silicone rubber in terms of oil resistance and high-temperature strength. When the two are blended, they form an intertwined or partially interpenetrating cross-linked network structure under irradiation or peroxide cross-linking, thus achieving a balance of flexibility, heat resistance, and high-temperature mechanical strength retention.

[0043] If the amount of methyl vinyl silicone rubber is too low, the material's flexibility and resilience will be insufficient; if the amount of fluoroelastomer is too low, the improvement in oil resistance and high-temperature mechanical properties will be limited. Therefore, this invention uses a ratio of 60-80 parts VMQ to 20-40 parts FKM, which is beneficial for meeting the requirements of high-voltage cables for new energy vehicles to be both heat-resistant and flexible in wiring.

[0044] The dosage of fumed silica is 20–40 parts. Fumed silica has a high specific surface area, which can reinforce silicone rubber systems and improve the tear resistance, tensile strength, and abrasion resistance of the insulation layer. For new energy vehicle cables, the insulation layer will be subjected to a lot of mechanical stress during installation, vibration, and thermal cycling. Adding fumed silica can improve the structural integrity of the insulation layer.

[0045] The preferred nano-boron nitride is hexagonal boron nitride with a particle size of 100–300 nm and a dosage of 5–20 parts, preferably 8–15 parts. Hexagonal boron nitride has high in-plane thermal conductivity and good electrical insulation properties, making it particularly suitable for thermal conductivity modification of cable insulation materials.

[0046] In the composite heat-resistant insulation layer 2, nano-boron nitride is uniformly dispersed within the VMQ / FKM blend matrix, forming discrete or semi-continuous microscopic thermal conductivity pathways. When conductor 1 generates Joule heating due to a large current, the heat can be transferred outward more quickly through the composite heat-resistant insulation layer containing nano-boron nitride, thereby reducing the local temperature of the insulation material near the conductor. Since the thermal aging rate of insulation materials typically increases significantly with increasing temperature, reducing the actual operating temperature can effectively extend the life of the insulation layer.

[0047] When the amount of nano-boron nitride is too low, the thermal conductivity is insufficient; when the amount is too high, it may affect the material's flexibility and extrusion processability. Therefore, this invention uses a range of 5 to 20 parts, preferably 8 to 15 parts, to balance thermal conductivity and mechanical flexibility.

[0048] The preferred particle size of nano-cerium oxide is 20–80 nm, and the dosage is 1–5 parts, preferably 2–3 parts. The Ce³ content in cerium oxide... + / Ce 4+Variable valence states can capture free radicals in high-temperature thermal oxidation environments, inhibiting the chain reaction of polymer molecular chain thermal oxidative degradation. For silicone rubber and fluoroelastomer blends, prolonged high temperatures can lead to side chain oxidation, main chain breakage, or changes in cross-linking structure; the addition of nano-cerium oxide can delay these processes.

[0049] Therefore, nano-cerium oxide is not merely a filler, but rather functions as an active thermal stabilizer. Combined with nano-boron nitride, it forms a dual thermal stabilization mechanism: nano-boron nitride provides thermal conductivity and cooling, while nano-cerium oxide captures free radicals for anti-aging.

[0050] The silane coupling agent can be vinyltrimethoxysilane, vinyltriethoxysilane, aminosilane, or epoxysilane, and the dosage is 1-3 parts. The silane coupling agent can improve the dispersibility and interfacial bonding of nano-boron nitride, nano-cerium oxide, and fumed silica in VMQ / FKM blend matrix. One end can interact with the hydroxyl groups or active sites on the surface of inorganic fillers, while the other end can achieve compatibility or grafting with the rubber matrix during crosslinking.

[0051] The preferred crosslinking agent is 2,5-dimethyl-2,5-di-tert-butylperoxide, used in an amount of 0.5 to 2 parts. Adding the crosslinking agent in the later stages of mixing can prevent premature crosslinking, which would lead to processing difficulties. Through subsequent irradiation crosslinking and / or peroxide crosslinking, a stable crosslinked network can be formed in the VMQ / FKM system.

[0052] A thermally conductive transition layer 3 is disposed between the composite heat-resistant insulation layer 2 and the shielding / heat dissipation composite layer 4, with a thickness of 0.1–0.5 mm. The thermally conductive transition layer 3 can be a thermally conductive silicone grease layer or a thermally conductive elastomer layer, which includes a silicone rubber matrix, spherical alumina filler, and a transition layer of nano-boron nitride.

[0053] The main functions of the thermally conductive transition layer 3 are twofold: first, to fill the microscopic gaps that may exist between the outer surface of the composite heat-resistant insulation layer 2 and the metal braided layer, thereby reducing the interfacial thermal resistance; second, to act as an elastic buffer layer to alleviate the stress caused by the difference in thermal expansion coefficients between the rubber insulation layer and the metal shielding layer.

[0054] The spherical alumina filler particle size is preferably 1–10 μm, which has good thermal conductivity and filling flowability. A small amount of nano-boron nitride further improves the continuity of the heat conduction path. The thermal conductivity of the thermal transition layer 3 is preferably not less than 1.5 W / m·K, so that it can transfer heat without significantly increasing the bending stiffness of the cable.

[0055] The shielding / heat dissipation composite layer 4 includes a nickel-plated copper wire braided layer 41 and a thermally conductive graphite tape layer 42. The nickel-plated copper wire braided layer 41 is disposed on the outside of the thermally conductive transition layer 3, with a braiding density of not less than 85%. Its main function is to provide electromagnetic shielding and form a metal thermally conductive network. The nickel-plated copper wire can improve high-temperature oxidation resistance, avoiding the increase in resistance and decrease in shielding performance caused by the oxidation of ordinary copper wire in high-temperature environments.

[0056] A thermally conductive graphite tape layer 42 is disposed on the outside of the nickel-plated copper wire braided layer 41, and can be spirally wrapped or longitudinally wrapped. The thickness of the thermally conductive graphite tape layer 42 is 0.1-0.3 mm, and the in-plane thermal conductivity is not less than 300 W / m·K. The function of the thermally conductive graphite tape layer 42 is to diffuse the point-like or linear heat collected by the nickel-plated copper wire braided layer 41 along the axial and circumferential directions of the cable, so that the heat is transformed from local concentration to planar distribution, thereby increasing the effective heat dissipation area of ​​the cable's outer surface and reducing local hot spots.

[0057] In the spiral wrapping embodiment, adjacent edges of the thermally conductive graphite tape layer 42 may have overlapping areas 43 to ensure thermal continuity. In the longitudinal wrapping embodiment, the graphite tape wraps along the cable axis, and the longitudinal overlapping edges are pressed and fixed by the outer sheath layer 5 to prevent displacement during operation and bending.

[0058] The outer sheath layer 5 is located outside the shielding / heat dissipation composite layer 4 to protect the internal structure. The outer sheath layer 5 can be made of irradiated cross-linked polyolefin or silicone rubber, and may contain small amounts of nano-boron nitride, flame retardants, antioxidants, and abrasion-resistant additives. The outer sheath layer 5 should meet the requirements for oil resistance, abrasion resistance, flame retardancy, weather resistance, and color identification. For high-voltage cables in new energy vehicles, the outer sheath layer can typically be designed in orange to meet the identification requirements of high-voltage wiring harnesses.

[0059] The outer sheath layer 5 should not be too thick, so as not to affect heat dissipation efficiency; nor should it be too thin, so as not to affect wear resistance and mechanical protection. Therefore, the appropriate sheath thickness can be selected according to the cable specifications.

[0060] See Figures 1-3 As shown, the present invention also provides a high-temperature thermal stabilization method for new energy vehicle cables, used to prepare the aforementioned cables.

[0061] Step S1: Preparation of composite heat-resistant insulation material Methyl vinyl silicone rubber and fluoroelastomer are fed into an internal mixer and mixed at 120–150°C for 5–10 minutes to form a homogeneous blend. Subsequently, fumed silica, nano boron nitride, nano cerium oxide, and silane coupling agent are added sequentially, and mixing continues for 15–20 minutes to ensure uniform dispersion of the nanofiller and reinforcing filler.

[0062] During this mixing process, the silane coupling agent improves the interfacial compatibility between nano-boron nitride and nano-cerium oxide and the rubber matrix, reducing filler agglomeration. After mixing, the system is cooled to below 80°C before adding the crosslinking agent to prevent premature decomposition at high temperatures. Subsequently, the mixture is sheeted, cooled, and pelletized using a two-roll mill to obtain the composite heat-resistant insulation material.

[0063] Step S2: Extrusion of composite heat-resistant insulation layer The composite heat-resistant insulating material is added to the extrusion equipment and coated around the conductor 1 to form a composite heat-resistant insulating layer 2. The extrusion temperature can be set as follows: feeding section 100~120℃, plasticizing section 130~160℃, homogenizing section 150~180℃, and die head 160~180℃.

[0064] During the extrusion process, it is essential to ensure that the insulation layer has a uniform thickness, a smooth surface, and is free of air bubbles and eccentricity. For cables with an inner semiconductive shielding layer 6, the inner semiconductive shielding layer 6 can be extruded first outside the conductor 1, followed by the extrusion of the composite heat-resistant insulation layer 2.

[0065] Step S3: Crosslinking treatment The extruded insulated wire cores are cross-linked by electron beam irradiation at a dose of 80–200 kGy. Irradiation cross-linking enables the VMQ / FKM blend system to form a more stable cross-linked network structure, while also allowing the silane coupling agent at the interface to participate in co-cross-linking or enhance bonding, making the filler less prone to migration or interface defects during high-temperature operation.

[0066] When the irradiation dose is too low, the degree of cross-linking is insufficient, resulting in poor heat deformation resistance; when the irradiation dose is too high, it may lead to excessive cross-linking of the material and a decrease in flexibility. Therefore, 80–200 kGy is a more suitable range.

[0067] Step S4: Formation of thermally conductive transition layer A thermally conductive transition layer 3 is coated or co-extruded around the outer periphery of the composite heat-resistant insulation layer 2. If coating is used, thermally conductive silicone grease or curable thermally conductive silicone rubber can be used; if co-extrusion is used, thermally conductive elastomer material can be extruded around the outer periphery of the composite heat-resistant insulation layer 2.

[0068] The thermally conductive transition layer 3 should be continuous and of uniform thickness to avoid local defects that could lead to an increase in interfacial thermal resistance.

[0069] Step S5: Preparation of shielding / heat dissipation composite layer First, nickel-plated copper wire is braided around the outer periphery of the thermally conductive transition layer 3 using a braiding device to form a nickel-plated copper wire braided layer 41. The braiding density should be no less than 85% to ensure the shielding effect and thermal conductivity continuity.

[0070] Subsequently, a thermally conductive graphite tape is wrapped or longitudinally wrapped around the outside of the nickel-plated copper wire braided layer 41 using a wrapping device to form a thermally conductive graphite tape layer 42. The thermally conductive graphite tape should be continuously wrapped, and overlapping areas 43 can be provided to reduce heat dissipation interruptions.

[0071] Step S6: Extrusion of the outer sheath layer An outer sheath layer 5 is extruded around the outer periphery of the shielding / heat dissipation composite layer 4. The outer sheath layer 5 can be made of irradiated cross-linked polyolefin or silicone rubber. If irradiated cross-linked polyolefin is used, irradiation cross-linking treatment can be performed after the outer sheath is extruded to improve heat resistance and oil resistance.

[0072] After the cable is manufactured, it can undergo high-temperature aging testing, thermal cycling testing, insulation resistance testing, breakdown strength testing, bending performance testing, and temperature difference testing from conductor to outer surface to evaluate the overall performance of the cable.

[0073] Example 1 Conductor 1 uses 50mm² nickel-plated copper stranded wire. In the composite heat-resistant insulation layer 2, VMQ is 70 parts, FKM is 30 parts, fumed silica is 30 parts, nano boron nitride is 10 parts, nano cerium oxide is 2 parts, vinyltrimethoxysilane is 1.5 parts, and crosslinking agent is 1 part.

[0074] The insulating material was mixed in an internal mixer at 135°C for 8 minutes, then the filler was added and mixing continued for 18 minutes. The mixture was then cooled to below 80°C and a crosslinking agent was added. After extrusion, the insulating layer underwent electron beam irradiation crosslinking at a dose of 120 kGy. The thermally conductive transition layer 3 was 0.3 mm thick with a thermal conductivity of approximately 1.8 W / m·K. The nickel-plated copper wire braided layer 41 had a braid density of 88%, and the thermally conductive graphite tape layer 42 was 0.2 mm thick with an in-plane thermal conductivity of not less than 300 W / m·K.

[0075] The resulting cable is suitable for high-voltage connection lines in the main circuit of new energy vehicles, and has good high-temperature resistance, flexibility and heat dissipation performance.

[0076] Example 2 Conductor 1 is made of 70mm² nickel-plated copper stranded wire, and an inner semiconductive shielding layer 6 is set on the outside of the conductor. In the composite heat-resistant insulation layer 2, VMQ is 65 parts, FKM is 35 parts, fumed silica is 35 parts, nano boron nitride is 15 parts, nano cerium oxide is 3 parts, silane coupling agent is 2 parts, and crosslinking agent is 1.2 parts.

[0077] The thermally conductive transition layer 3 is formed by co-extrusion of a thermally conductive elastomer and has a thickness of 0.4 mm. In the shielding / heat dissipation composite layer 4, the nickel-plated copper wire braiding density is 90%, and the thermally conductive graphite tape is arranged in a longitudinal wrapping manner. This embodiment is suitable for the connection line between a battery pack and a motor controller, where the continuous current carrying capacity is high and the risk of heat accumulation is significant.

[0078] Example 3 Conductor 1 uses 35mm² silver-plated copper stranded wire. In the composite heat-resistant insulation layer 2, VMQ comprises 78 parts, FKM 22 parts, fumed silica 25 parts, nano boron nitride 8 parts, nano cerium oxide 2 parts, silane coupling agent 1.5 parts, and crosslinking agent 0.8 parts. This embodiment has a higher VMQ ratio, resulting in better flexibility and suitability for vehicle-mounted high-voltage branch line cables with limited wiring space and small bending radius requirements.

[0079] Comparative Example 1 uses ordinary silicone rubber insulation without adding nano-boron nitride and nano-cerium oxide, and also omits a thermally conductive transition layer and a thermally conductive graphite tape layer. Under continuous high-temperature current-carrying conditions, the insulation layer near the conductor reaches a high temperature, and the elongation decreases significantly after thermal aging.

[0080] Comparative Example 2 uses a VMQ / FKM blend insulation layer with added nano-boron nitride, but without added nano-cerium oxide. This cable exhibits improved thermal conductivity, but the molecular chain degradation of the insulation material is still significant after long-term thermo-oxidative aging, resulting in a lower thermal aging retention rate compared to the embodiments of this invention.

[0081] Comparative Example 3 uses a composite heat-resistant insulation layer and a metal braided shielding layer, but does not include a thermally conductive transition layer or a thermally conductive graphite tape layer. Due to the large interfacial thermal resistance between the insulation layer and the braided layer, and because the metal braided layer only forms linear thermal conduction paths, the outer surface temperature distribution is uneven, and the improvement of local hot spots is limited.

[0082] As can be seen from the above embodiments and comparative examples, the present invention, through the synergistic design of material modification and structural heat dissipation, can more effectively reduce the internal temperature rise of the cable, delay the thermal aging of the insulation layer, and improve the long-term reliability of high-voltage cables for new energy vehicles in high-temperature environments.

[0083] This invention is applicable to high-voltage cables for new energy vehicles, and can also be used in energy storage systems, high-temperature industrial equipment, high-voltage cables for rail transit, high-current cables for charging piles, and other cable products with high requirements for high temperature resistance and heat dissipation performance. In practical applications, the conductor cross-sectional area, the amount of nano-boron nitride added, the thickness of the thermally conductive transition layer, the braiding density, and the thickness of the graphite tape can be adjusted according to the current carrying capacity, wire diameter, wiring space, temperature resistance rating, and flexibility requirements.

[0084] The high-temperature thermally stable cable for new energy vehicles and its preparation method provided by this invention establish an efficient cascaded heat dissipation path from the conductor to the outer sheath through the synergistic cooperation of VMQ / FKM blend matrix, nano boron nitride, nano cerium oxide, thermally conductive transition layer, nickel-plated copper wire braided layer and thermally conductive graphite tape layer, while improving the thermal and oxygen aging resistance and interface stability of the insulation material. This can significantly improve the long-term safety performance of high-voltage cables for new energy vehicles in high-temperature environments.

[0085] The above embodiments merely illustrate several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this patent should be determined by the appended claims.

Claims

1. A high-temperature thermally stable cable for new energy vehicles, characterized in that, The system comprises, from the inside out, a conductor (1), a composite heat-resistant insulation layer (2), a thermally conductive transition layer (3), a shielding / heat dissipation composite layer (4), and an outer sheath layer (5); the composite heat-resistant insulation layer (2) comprises a silicone rubber / fluoroelastomer blend matrix, fumed silica, nano boron nitride, nano cerium oxide, silane coupling agent, and crosslinking agent; the thermally conductive transition layer (3) is disposed between the composite heat-resistant insulation layer (2) and the shielding / heat dissipation composite layer (4) to reduce the interfacial thermal resistance between the composite heat-resistant insulation layer (2) and the shielding / heat dissipation composite layer (4); the shielding / heat dissipation composite layer (4) comprises a nickel-plated copper wire braided layer (41) and a thermally conductive graphite tape layer (42); The composite heat-resistant insulation layer (2), the thermally conductive transition layer (3), and the shielding / heat dissipation composite layer (4) together form a stepped heat conduction and heat dissipation path that conducts heat from the conductor (1) to the outer sheath layer (5).

2. The high-temperature thermally stable cable for new energy vehicles according to claim 1, characterized in that, The conductor (1) is bare copper stranded wire, nickel-plated copper stranded wire or silver-plated copper stranded wire, and the conductor cross-sectional area is 16 to 120 mm²; the conductor (1) is nickel-plated copper stranded wire.

3. The high-temperature thermally stable cable for new energy vehicles according to claim 1, characterized in that, It also includes an inner semiconductive shielding layer (6), which is disposed between the conductor (1) and the composite heat-resistant insulation layer (2) to homogenize the electric field on the conductor surface and reduce the local electric field concentration caused by the conductor stranding gap.

4. The high-temperature thermally stable cable for new energy vehicles according to claim 1, characterized in that, The silicone rubber / fluoroelastomer blend matrix includes methyl vinyl silicone rubber and fluoroelastomer. Based on a total weight of 100 parts of methyl vinyl silicone rubber and fluoroelastomer, the methyl vinyl silicone rubber comprises 60 to 80 parts and the fluoroelastomer comprises 20 to 40 parts. Based on a total weight of 100 parts of the methyl vinyl silicone rubber and fluoroelastomer, the composite heat-resistant insulating layer (2) further includes: 20-40 parts of fumed silica; 5-20 parts of nano boron nitride; 1-5 parts of nano-cerium oxide; 1-3 parts of silane coupling agent; Crosslinking agent 0.5-2 parts; The nano-boron nitride is hexagonal boron nitride with a particle size of 100–300 nm. The particle size of the nano-cerium oxide is 20–80 nm; The silane coupling agent is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, aminosilane, and epoxysilane; The crosslinking agent is 2,5-dimethyl-2,5-di-tert-butylperoxide.

5. The high-temperature thermally stable cable for new energy vehicles according to claim 1, characterized in that, The thickness of the thermally conductive transition layer (3) is 0.1 to 0.5 mm; The thermally conductive transition layer (3) is a thermally conductive silicone grease layer or a thermally conductive elastomer layer. The thermally conductive transition layer (3) includes a silicone rubber matrix, spherical alumina filler and nano boron nitride. The particle size of the spherical alumina filler is 1 to 10 μm. The thermal conductivity of the thermally conductive transition layer (3) is not less than 1.5 W / m·K.

6. The high-temperature thermally stable cable for new energy vehicles according to claim 1, characterized in that, The braiding density of the nickel-plated copper wire braided layer (41) is not less than 85%; The thermally conductive graphite tape layer (42) is wrapped around or longitudinally wrapped around the outside of the nickel-plated copper wire braided layer (41). The thickness of the thermally conductive graphite tape layer (42) is 0.1 to 0.3 mm, and the in-plane thermal conductivity is not less than 300 W / m·K. The thermally conductive graphite tape layer (42) is spirally wrapped along the cable axis, and the adjacent wrapping edges have an overlap area; or, the thermally conductive graphite tape layer (42) is longitudinally wrapped along the cable axis, and the outer side of the longitudinal wrapping overlap edge is pressed and fixed by the outer sheath layer (5).

7. The high-temperature thermally stable cable for new energy vehicles according to claim 1, characterized in that, The outer sheath layer (5) is an irradiated cross-linked polyolefin sheath layer or a silicone rubber sheath layer, and the outer sheath layer (5) also includes one or more of nano boron nitride, flame retardant, antioxidant and wear-resistant additive.

8. The high-temperature thermally stable cable for new energy vehicles according to claim 1, characterized in that, The composite heat-resistant insulation layer (2) is cross-linked by electron beam irradiation to form a cross-linked network structure, and the long-term temperature resistance of the cable is not lower than 150℃.

9. A method for high-temperature thermal stability of cables for new energy vehicles, characterized in that, The method for preparing the high-temperature thermally stable cable for new energy vehicles according to any one of claims 1 to 8 includes the following steps: S1. Preparation of composite heat-resistant insulation material: Methyl vinyl silicone rubber and fluoroelastomer are put into a mixing equipment and mixed at 120-150℃ for 5-10 minutes. Then, fumed silica, nano boron nitride, nano cerium oxide and silane coupling agent are added in sequence and mixed for another 15-20 minutes. After cooling, a crosslinking agent is added. After thinning, cooling and pelletizing, the composite heat-resistant insulation material is obtained. S2, Extrusion of composite heat-resistant insulation layer (2): The composite heat-resistant insulation material is coated on the outer periphery of the conductor (1) through an extrusion device to form a composite heat-resistant insulation layer (2); S3, Crosslinking treatment: Electron beam irradiation crosslinking is performed on the insulating core that forms the composite heat-resistant insulating layer (2); S4. Forming a thermally conductive transition layer (3): Coating or co-extruding a thermally conductive transition layer (3) around the outer periphery of the composite heat-resistant insulating layer (2); S5. Forming a shielding / heat dissipation composite layer (4): Nickel-plated copper wire is first braided on the outer periphery of the thermally conductive transition layer (3) to form a nickel-plated copper wire braided layer (41), and then wrapped or longitudinally wrapped with thermally conductive graphite tape to form a thermally conductive graphite tape layer (42). S6. Extruded outer sheath layer (5): An outer sheath layer (5) is extruded around the outer periphery of the shielding / heat dissipation composite layer (4).

10. The high-temperature thermal stability method for new energy vehicle cables according to claim 9, characterized in that, In step S2, the extrusion temperature of the composite heat-resistant insulation layer (2) is: 100-120℃ in the feeding section, 130-160℃ in the plasticizing section, 150-180℃ in the homogenizing section, and 160-180℃ in the die head. In step S3, the irradiation dose for electron beam crosslinking is 80–200 kGy; After step S6, the process also includes irradiating crosslinking treatment of the outer sheath layer (5) and / or performing high-temperature aging test, thermal cycling test, insulation resistance test and conductor-to-outer surface temperature difference test on the resulting cable.